The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/030089161009600102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Intensified Neoadjuvant Treatment and Standard Preoperative Chemoradiation for Rectal Cancer

Abstract: Our data seem to correlate the addition of oxaliplatin to the standard treatment for rectal cancer with higher rates of sphincter preservation, down-staging and complete response. Toxicity is increased and requires careful monitoring. However, our results refer to a retrospective comparison of a small series of patients and need to be validated by the large, phase III randomized trial currently ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, no major impact has been shown with the incidence of dermatological effects (Musio et al . ). In a study, to evaluate the addition of a chemotherapy drug (oxaloplatin) to the standard neoadjuvant protocol of radiotherapy and chemotherapy (5‐fluorouracil), the incidence of grade 3 radiation dermatitis was 23·8% in patients following the standard protocol and 20% in patients receiving oxaloplatin in addition to this (Musio et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, no major impact has been shown with the incidence of dermatological effects (Musio et al . ). In a study, to evaluate the addition of a chemotherapy drug (oxaloplatin) to the standard neoadjuvant protocol of radiotherapy and chemotherapy (5‐fluorouracil), the incidence of grade 3 radiation dermatitis was 23·8% in patients following the standard protocol and 20% in patients receiving oxaloplatin in addition to this (Musio et al .…”
Section: Resultsmentioning
confidence: 97%
“…In a study, to evaluate the addition of a chemotherapy drug (oxaloplatin) to the standard neoadjuvant protocol of radiotherapy and chemotherapy (5‐fluorouracil), the incidence of grade 3 radiation dermatitis was 23·8% in patients following the standard protocol and 20% in patients receiving oxaloplatin in addition to this (Musio et al . ). It can therefore be concluded that the addition of this chemotherapy drug did not exacerbate the development of radiation dermatitis.…”
Section: Resultsmentioning
confidence: 97%
“…Pain appears to occur to some extent in a small number of patients, although it seems to be at a tolerable level, as no interruption to treatment occurred in these instances, with the exception of one particular study (Marijnen et al 2002). It must be noted however that the sample size was much larger in this study (n = 1530) than in the other investigations that monitored pain levels (highest n = 180; Hwang et al 2002), and also, the authors introduced their own tool to measure this symptom, without stating whether it had proven validity and reliability (Hwang et al 2002, Marijnen et al 2002, Guren et al 2003, Radu et al 2008, Carlomagno et al 2009, Musio et al 2010, Oh & Seo 2011.…”
Section: Introductionmentioning
confidence: 78%
“…Prevalence rates of diarrhoea may also be affected by differences in treatment protocols, as the study by Bosset et al (2006) reported higher rates of this symptom in patients that received chemotherapy and radiotherapy, rather than radiotherapy alone (37Á6% vs 17Á3%). However, the addition of chemotherapy did not have any impact on rates of dermatological issues (Musio et al 2010). Nonetheless, it must be noted that although doses of radiotherapy were similar in the majority of studies that assessed these symptoms, there were differences in the chemotherapy regime patients received, thereby making it difficult to accurately compare the resulting symptoms.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation